Epistemologi Keilmuan Kalam dan Fikih dalam Merespon Perubahan di Era Negara-Bangsa dan Globalisasi (Pemikiran Filsafat Keilmuan Agama Islam Jasser Auda) - M. Amin Abdullah (Sharia and Law Faculty, 2012)
Clumps of Islamic scholarship include, among others, Kalam, Tafsir, Hadith, Fiqh, Philosophy, Mysticism. Also can be added Ulum al-Qurâ€™an, Ulum al-Hadith, Arabic with it various branches. In terms of â€œKalamâ€, often more popularly called Aqeedah, Fiqh is called Shariah and Sufism called Akhlaq. Thus, the Islamic religious sciences trilogy as found in Islamic religious education in schools covering Aqidah - actually a discussion on Kalam/ theology, Worship-represented by Fiqh or Shariah-and Akhlaq-whose roots are Tasawwuf. Internal relationships between all disciplines of Islamic sciences are often interrelated, because they are actually could not be segregated and separated. This kind of Islamic sciences relationship are not alike with the relationship between Mathematics, Sociology and Law where their discussions can really be separated, meanwhile the relationships among Islamic sciences indeed interrelated to one another. In such approach, then when the paper titled â€˜Kalamâ€™, in fact it discusses very indirectly related to the discussion of Fiqh / Shariâ€˜ah, Philosophy and Mysticism. When mentioned â€œKalamâ€ here means a way of life or view of religious Islamic World, which includes a variety of many disciplines in Islamic sciences. This paper is going to discuss Jasser Audaâ€™s idea to answer the questions: whether the world view of Islam colored Religiously static (ghairu qabilin li al-niqash wa al-taghyir) or vice versa, the Islamic religious world view actual dynamic (qabilun li al-niqash wa al-taghyir) so that the concepts, understanding and interpretation of the old and new can be moved on a dialogue and discussion without unnecessary tension because of the history of human development and history of Muslims continues and always on the move and change according to the motion of the universe, as in fact the planet is spinning move as the movement and rotation of the other planets. In this paper, â€œKalamâ€ will be seen in the context of historical changes in human experience, from the traditional era, then how in the modern and postmodern as well as contemporary Muslim intellectuals, as Jasser Auda react it and how about the form or format Kalam world view in a nation-state era and in the global era like nowadays. What are the implications and consequences on education, propaganda, social- community relations, politics and so on.